Analisis Teritorialitas Ruang Hunian pada Permukiman Padat di Kota Lhokseumawe: Studi Kasus Kampung Jawa Lama - Nuri, Zulfa; Fahrizal, Effan; Saputra, Eri; Mirsa, Rinaldi (Universitas muhammadiyah palembang, 2023)
Kampung Jawa Lama is one of the villages in the city of Lhokseumawe, which has a dense population. An unbalanced comparison between the availability of urban space and the increasing number of residents impacts community space activities. This research study is focused on the old Javanese village settlements, which have ambiguity between the boundaries of space for activities such as private space and public space in everyday life in society. It can be seen from community activities that use public space for personal gain. The spatial boundaries in the old Javanese village occur because they grow and develop irregularly, resulting in social interaction factors and community activities that dominate the space. This research uses a descriptive qualitative survey method that is exploratory with a rationalistic approach. The characteristics of territoriality can be seen from the influence of the components in the space, where the function has its role in the emergence of activities. Community agreements with supporting elements for activities such as activities around residential spaces, routine activities, and scheduled activities also form territories that occur in the settlements of Kampung Jawa Lama. In addition, the activities that occur cause a change in the function of the public space used for personal interests by residents in the neighborhood around the house.